Morpho-economical Indicators of Some Local and Foreign Soybean Varieties Planted as Main Crops - Mokhichekhra Azamatovna, Kholiqova; Khilola Khudoybergenovna, Matniyazova; Gulnoza Sayfullaevna, Ismagilova (International Journal of Psychosocial Rehabilitation, 2020)
This article examines the number of legumes per plant, which is one of the most important morphoeconomical features of soybean varieties grown as the main crop in the Samarkand region. According to the data obtained, the highest number of legumes was recorded in foreign varieties Nena R 1 from Kazakhstan, Sparta from Russia, and Orzu from local varieties.